Nobilitowanie ideologii społecznych przy pomocy nauki (ideologizowanie nauki) - analizy i refleksje = Ennobling social ideologies by means of science (ideologizing of science) - analysis and reflections - Kowalski, Mirosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article introduces the issues of ideology in social sciences (including education). Understanding only the ideal (although often unreliable in practical use) character of criteria, in terms of differentiating science from ideology, the author has analysed the phenomenon of ideology in the area of assumptions and assertions in contemporary social sciences.
Keywords: nauki społeczne; ideologia a nauka